2018
DOI: 10.1016/j.athoracsur.2018.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Small Chest Wall Defects Caused by Tubercular Abscesses Using Two Different Flaps

Abstract: Tubercular infection of the chest wall is rare and typically progresses to abscess formation. Treatment of these abscesses combines medical therapy with surgical debridement, which can cause defects of various sizes. This case report describes reconstruction of relatively small chest wall defects caused by tubercular abscesses with the use of two different flaps: a lateral intercostal artery perforator flap and a split pectoralis major muscle flap. The use of these flap techniques may provide a novel approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…For patients with large tissue defect after debridement, pedicled myocutaneous flap with good blood supply should be used to fill the chest wall defect [ 23 , 24 ]. Since the patient has undergone total mastectomy for breast cancer, and the nearby pectoralis major muscle and surrounding tissues are weak, we chose the latissimus dorsi myocutaneous flap with close anatomical location and abundant blood supply to repair the huge chest wall defect [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with large tissue defect after debridement, pedicled myocutaneous flap with good blood supply should be used to fill the chest wall defect [ 23 , 24 ]. Since the patient has undergone total mastectomy for breast cancer, and the nearby pectoralis major muscle and surrounding tissues are weak, we chose the latissimus dorsi myocutaneous flap with close anatomical location and abundant blood supply to repair the huge chest wall defect [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After operation, the color of the skin paddle can be observed regularly and the blood supply can be understood in time.Tissue aps commonly used in clinic include muscle ap, myocutaneous ap, greater omentum and so on [9,10].In order to eliminate the chest wall tissue defect caused by debridement, increase local blood supply, improve local tissue healing and anti infection ability are very important. For patients with large tissue defect after debridement, pedicled myocutaneous ap with good blood supply should be used to ll the chest wall defect [11,12].Since the patient has undergone total mastectomy for breast cancer, and the nearby pectoralis major muscle and surrounding tissues are weak, we chose the latissimus dorsi myocutaneous ap with close anatomical location and abundant blood supply to repair the huge chest wall defect [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…After operation, the color of the skin paddle can be observed regularly and the blood supply can be understood in time.Tissue aps commonly used in clinic include muscle ap, myocutaneous ap, greater omentum and so on [9,10].In order to eliminate the chest wall tissue defect caused by debridement, increase local blood supply, improve local tissue healing and anti infection ability are very important. For patients with large tissue defect after debridement, pedicled myocutaneous ap with good blood supply should be used to ll the chest wall defect [11,12].Since the patient has undergone total mastectomy for breast cancer, and the nearby pectoralis major muscle and surrounding tissues are weak, we chose the latissimus dorsi myocutaneous ap with close anatomical location and abundant blood supply to repair the huge chest wall defect [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The leading causes of lesion recurrence or unhealed incision include incomplete removal of the abscess, failure to resecting the damaged lesions on the ribs, and insufficient anti-TB treatment. Kim et al concluded that complete abscess removal (including the resection of the affected chest wall) could reduce surgical risk and reduce recurrence (8). They also recommend the complete removal of abscesses (including resection of necrotic ribs and cartilage) because the abscess may also affect the deep tissues.…”
Section: Inputs From Thoracic Surgeons Dr Hongliang Bianmentioning
confidence: 99%